Intracerebroventricular Administration of Interferon-Alpha Induced Depressive-Like Behaviors and Neurotransmitter Changes in Rhesus Monkeys - Li, Zhifei; Li, Zhaoxia; Lv, Xiaoman; Li, Zhaofu; Xiong, Lei; Hu, Xintian; Qin, Dongdong (Frontiers in Neuroscience, 2020)
Interferon-alpha (IFN-α) is a cytokine widely used in the treatment of brain cancers and virus infections with side effects including causing depression. Monoamine neurotransmitter systems have been found playing important roles in peripheral IFN-α induced depression, but how peripheral IFN-α accesses the central nervous system and contributes to the development of depression is poorly known. This study aimed to develop a nonhuman primate model using long-term intracerebroventricular (i.c.v.) administration of IFN-α (5 days/week for 6 weeks), to observe the induced depressive-like behaviors and to explore the contributions of monoamine neurotransmitter systems in the development of depression. In monkeys receiving i.c.v. IFN-α administration, anhedonia was observed as decreases of sucrose consumption, along with depressive-like symptoms including increased huddling behavior, decreases of spontaneous and reactive locomotion in home cage, as well as reduced exploration and increased motionless in the open field. Chronic central IFN-α infusion significantly increased the cerebrospinal fluid (CSF) concentrations of noradrenaline (NA) and 3,4-dihydroxyphenylacetic acid (DOPAC), but not 5-Hydroxyindoleacetic acid (5-HIAA) and homovanillic acid (HVA). These CSF monoamine metabolites showed associations with some specific depression-related behavior. In conclusion, central IFN-α administration induced anhedonia and depression-related behaviors comparable to the results with peripheral administration, and the development of depression was associated with the dysfunction of monoamine neurotransmitters.